Greater Trochanteric Fracture with Lesser Trochanter Extension: A Report of 2 Cases and CT-Based Finite Element Analysis. Issue 3 (July 2021) - Yukata, Kiminori; Uchiyama, Yuya; Nishida, Norihiro; Ohgi, Junji; Sakai, Takashi; Fujii, Hiroshi
Abstract : Case: Two patients (aged 71 and 82 years) presented with a greater trochanteric fracture with lesser trochanter extension. These cases were successfully treated by prophylactic osteosynthesis to prevent secondary intertrochanteric/cervical fracture and to facilitate an early return to daily life. We also clarified the mechanical strength of the area that escaped bone fracture using the patient-specific computed tomography–based finite element method (CT/FEM). Conclusions: The present fractured femurs were shown to halve the axial compression strength and had only one-sixth torsional strength in patient-specific CT/FEM. These data support prophylactic surgery to prevent the secondary fractures because of this injury.